Young Children Respond to Moral Dilemmas Like Their Mothers - Dworazik, Niklas; Kärtner, Joscha; Lange, Leon; Köster, Moritz (Frontiers in Psychology, 2019)
There is a large scientific interest and debate on human moral judgements. However, little is known about the developmental origins and the specific role of the primary caregivers in the early development of inter-individual differences in human morality. Here we assess the moral intuitions of 3- to 6-year-old children and their mothers (N = 56), using child-friendly versions of five trolley scenarios and two control dilemmas. We found that children respond to moral dilemmas similar to the their mothers, revealed by correlations between the responses of mothers and their children in all five moral dilemmas and a highly similar overall response pattern between mother and child across all judgements. Furthermore, children’s response tendencies were similar to the response tendencies of adults. Thus similar moral principles (e.g. the Doctrine of the Double Effect) identified in adults, forming a universal moral grammar, may guide the moral intuitions in early childhood already. Taken together, the present findings provide the first evidence that children’s moral intuitions are closely associated with the moral intuitions of their mother.